Expression of GAD67 and Dlx5 in the Taste Buds of Mice Genetically Lacking Mash1. (28th March 2014) - Kito-Shingaki, Ayae; Seta, Yuji; Toyono, Takashi; Kataoka, Shinji; Kakinoki, Yasuaki; Yanagawa, Yuchio; Toyoshima, Kuniaki
Abstract : It has been reported that a subset of type III taste cells express glutamate decarboxylase (GAD)67, which is a molecule that synthesizes gamma-aminobutyric acid (GABA), and that Mash1 could be a potential regulator of the development of GABAnergic neurons via Dlx transcription factors in the central nervous system. In this study, we investigated the expression of GAD67 and Dlx in the embryonic taste buds of the soft palate and circumvallate papilla using Mash1 knockout (KO)/GAD67-GFP knock-in mice. In the wild-type animal, a subset of type III taste cells contained GAD67 in the taste buds of the soft palate and the developing circumvallate papilla, whereas GAD67-expressing taste bud cells were missing from Mash1 KO mice. A subset of type III cells expressed mRNA for Dlx5 in the wild-type animals, whereas Dlx5-expressing cells were not evident in the apical part of the circumvallate papilla and taste buds in the soft palate of Mash1 KO mice. Our results suggest that Mash1 is required for the expression of GAD67 and Dlx5 in taste bud cells.